The pH heterogeneity in human calf muscle during neuromuscular electrical stimulation. Issue 6 (20th July 2016) - Stutzig, Norman; Rzanny, Reinhard; Moll, Kevin; Gussew, Alexander; Reichenbach, Jürgen R.; Siebert, Tobias
Abstract : Purpose: The aim of the study was to examine pH heterogeneity during fatigue induced by neuromuscular electrical stimulation (NMES) using phosphorus magnetic resonance spectroscopy ( 31 P‐MRS). It is hypothesized that three pH components would occur in the 31 P‐MRS during fatigue, representing three fiber types. Methods: The medial gastrocnemius of eight subjects was stimulated within a 3‐Tesla whole body MRI scanner. The maximal force during stimulation (Fstim ) was examined by a pressure sensor. Phosphocreatine (PCr), adenosintriphosphate, inorganic phosphate (Pi), and the corresponding pH were estimated by a nonvolume‐selective 31 P‐MRS using a small loop coil at rest and during fatigue. Results: During fatigue, Fstim and PCr decreased to 27% and 33% of their initial levels, respectively. In all cases, the Pi peak increased when NMES was started and split into three different peaks. Based on the single Pi peaks during fatigue, an alkaline (6.76 ± 0.08), a medium (6.40 ± 0.06), and an acidic (6.09 ± 0.05) pH component were observed compared to the pH (7.02 ± 0.02) at rest. Conclusion: It is suggested that NMES is able to induce pH heterogeneity in the medial gastrocnemius, and that the single Pi peaks represent the different muscle fiber types of the skeletal muscle. Magn Reson Med 77:2097–2106, 2017. © 2016 International Society for Magnetic Resonance in Medicine